KEWENANGAN KEPOLISIAN DALAM PENANGANAN UNJUK RASAANARKIS DI WILAYAH HUKUM POLDA BALI - I Nyoman Suryana, SH,MH (Universitas Mahendradatta, 2022)
Differences in principles in the state can affect demonstrations. Article 8 of Law Number 9 of 1998 confirms that the public has the right to participate in a responsible manner to make efforts to convey opinions in public in a safe, orderly and peaceful manner. However, in reality, this regulation is often not obeyed during demonstrations, resulting in anarchy. The problem in the research is regarding the authority of the police in handling anarchic demonstrations and the obstacles and efforts made in handling anarchic demonstrations that have an impact on security stability. This research uses normative legal research supported by empirical legal research, using primary, secondary, and tertiary legal materials. With a statutory approach, a fact approach, and a case approach. The result of the discussion is that the authority of the Bali Regional Police in law enforcement against anarchic demonstrations refers to Law Number 9 of 1998, whose handling is guided by Perkapolri Number Pol:16 of 2006, as well as its Services, Security, and Handling are guided by Perkapolri No. 9 of 2008. The Bali Regional Police constraint in dealing with anarchic demonstrations is internal constraints such as there are members who do not understand the applic ation of the rules and sometimes members cannot control their emotions as well as the delay in information on demonstrations. External obstacles include the person in charge of the demonstrators not seeking permission to protest, the infiltration of demonstrators without the knowledge of the person in charge, and demonstrators being influenced by alcohol. Efforts to handle cases of anarchic demonstrations are preventive measures such as socialization to the community and repressive efforts, namely law enforcement.